2017
DOI: 10.1159/000480402
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the S-1/Temozolomide Regimen in Patients with Metastatic Neuroendocrine Tumors

Abstract: Purpose: Both capecitabine alone and capecitabine in combination with temozolomide have activities against neuroendocrine tumors (NETs). However, the role of S-1 in NETs is still unknown. We performed a study to evaluate the safety and efficacy of the S-1/temozolomide (STEM) regimen in patients with locally advanced or metastatic NETs. Methods: A retrospective review was conducted in 20 patients with locally advanced or metastatic NETs treated with the STEM regimen. Of the patients, 15 (75.00%) had failed 1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…It was approved as an optional third-line treatment for refractory advanced non-small cell lung cancer (Han et al., 2018a,b; Chen, 2019 ; Zhou et al., 2019 ). Like other analogous agents, the most common adverse effects of AL are hypertension, triglyceride elevation, elevated thyroid-stimulating hormone (TSH) (Sun et al., 2016 ; Si et al., 2018 ; Zhao et al., 2018 ). The pattern of systemic administration determines the increase in local blood concentrations along with increased systemic cardiovascular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It was approved as an optional third-line treatment for refractory advanced non-small cell lung cancer (Han et al., 2018a,b; Chen, 2019 ; Zhou et al., 2019 ). Like other analogous agents, the most common adverse effects of AL are hypertension, triglyceride elevation, elevated thyroid-stimulating hormone (TSH) (Sun et al., 2016 ; Si et al., 2018 ; Zhao et al., 2018 ). The pattern of systemic administration determines the increase in local blood concentrations along with increased systemic cardiovascular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“… 15 We have previously reported that S-1 plus temozolomide has strong anti-tumour efficacy and is well tolerated in patients with locally advanced or metastatic NETS. 16 Thalidomide, an angiogenesis inhibitor that can suppress cell proliferation and tumour angiogenesis, has also shown an anti-tumour effect against NETS. 17 A phase II study demonstrated that temozolomide combined with thalidomide resulted in an overall ORR of 25%, and a 2-year survival rate of 70% in patients with metastatic NETS.…”
Section: Introductionmentioning
confidence: 99%